Manajemen Biaya dan Sarana Prasarana di SMA N 3 Pati dan MA Silahul Ulum Asempatan Trangkil Pati - Subaidi Subaidi (At-Tarbiyat, 2019)
This study described the management and infrastructure in high school n 3 starch and is silahul ulum asempapan trangkil starch.In this research used a qualitative approach descriptive.Data collection method through observation technique, interviews and documentation.Utilize non statistics and analysis.Conclusion in research are among others apply the principle of principle: the achievement of a goal, principle efficiency, administrative principle, principle clarity responsibility.The process of education facilities and infrastructure management closely related to planning: of education facilities andinfrastructure.Procurement of education facilities and infrastructure.Inventory of education facilities and infrastructure.Supervision and maintenance of education facilities and infrastructure.Pengahapusan school facilities and infrastructure madrasah /.Pengeloalan opersioanal to support the facilities of infrastructure in high school n 3 starch and is silahul ulum is a slight difference if silahul ulum manage endowments and productive,The students and contributions , while in high school and 3 starch come from the government anddonations were allocated to development students associated facilities and infrastructure.